Between Social Justice and Decolonisation: Exploring South African MOOC designers’ conceptualisations and approaches to addressing injustices [presentation, O-143] - Adam, Taskeen (The Care in Openness, 2020)
As social justice and decolonisation discussions fill the physical and virtual corridors of university spaces in South Africa, educators, and in this case, MOOC designers, are inevitably influenced by them. They are prompted to reflect on such topics, whether in agreement or with scepticism. Provoked by one interviewee’s comment that ‘you could decolonise and still have an enormous amount of injustice’, this paper investigates how South African MOOC designers conceptualise justices, and how they attempt to address these injustices in and through their MOOCs. As terminology from these discourses at times misconstrued MOOC designers’ opinions, an analytical framework was created to shift focus to addressing injustices, namely: material injustices, cultural-epistemic injustices, and political/geopolitical injustices. These Dimensions of Human Injustice were used to analyse semi-structured interviews with 27 MOOC South African designers. It was found that they formed opinions based on the aforementioned discourses, which impacted their engagement with injustice in their designs. Those who stressed cultural-epistemic injustices, focused on relevance, inclusive processes and the geopolitics of knowledge production. Those who stressed material injustices, focused on socio-economic disparities, infrastructural inequalities and the need to tackle these systemic problems at a societal level. Through highlighting MOOC designers’ attempts at addressing injustices, it is envisioned this will lead to more multi-dimensional, justice-oriented approaches to MOOC design that better enable learners. Additionally, efforts by South African MOOC designers, highlighted in this paper, can be seen as a guide for the MOOC space in general to take greater strides in creating MOOCs in more justice-oriented ways.
Keywords: Author:OpenDevEd